Immune tolerance promotion by LSEC-specific lentiviral vector-mediated expression of the transgene regulated by the stabilin-2 promoter - Ester Borroni; Chiara Borsotti; Roberta A. Cirsmaru; Vakhtang Kalandadze; Rosella Famà; Simone Merlin; Brian Brown; Antonia Follenzi (Elsevier, 2024)
Liver sinusoidal endothelial cells (LSECs) are specialized endocytic cells that clear the body from blood-borne pathogens and waste macromolecules through scavenger receptors (SRs). Among the various SRs expressed by LSECs is stabilin-2 (STAB2), a class H SR that binds to several ligands, among which endogenous coagulation products. Given the well-established tolerogenic function of LSECs, we asked whether the STAB2 promoter (STAB2p) would enable us to achieve LSEC-specific lentiviral vector (LV)-mediated transgene expression, and whether the expression of this transgene would be maintained over the long term due to tolerance induction. Here, we show that STAB2p ensures LSEC-specific green fluorescent protein (GFP) expression by LV in the absence of a specific cytotoxic CD8+ T cell immune response, even in the presence of GFP-specific CD8+ T cells, confirming the robust tolerogenic function of LSECs. Finally, we show that our delivery system can partially and permanently restore FVIII activity in a mouse model of severe hemophilia A without the formation of anti-FVIII antibodies. Overall, our findings establish the suitability of STAB2p for long-term LSEC-restricted expression of therapeutic proteins, such as FVIII, or to achieve antigen-specific immune tolerance in auto-immune diseases.